The Effect of Ankle Strategy Exercises on Static Balance in The Elderly - Dwi Yuniar Ramadhani; Putri Arivia (Universitas Nahdlatul Ulama Surabaya, 2021)
Decreased muscle strength is a musculoskeletal disorder in the elderly, resulting in slow movements and impaired physical mobility. Physical changes that occur in the elderly cause the risk of falling. This study analyzes the ankle strategy exercise's effect on static balance in the elderly at Regional Technical Implementation Unit (UPTD) Griya Werdha Surabaya. This study was Pre-Experimental with One Group Pre-Post Test Design. From the population, there were thirty-five respondents by simple random sampling. This study's independent variable was ankle strategy exercises with frequency three times a week within a month. The dependent variable was a static balance with the instrument Time Up Go (TUG) test. The authors analyzed the data with the Wilcoxon test. The study results showed a significant effect of the ankle strategy exercise on static balance in the elderly (p=0,000). The result showed a decrease in the number of elderly who have the high-risk of falling before the ankle strategy exercise (60% of elderly have a high risk of falling) and after the intervention (34% of elderly have a decreased risk of falling). The elderly should do the ankle strategy exercise independently or with assistant three times a week to improve their static balance and decrease their high-risk of falls.